Comparative study for catalytic cracking of model bio-oil and palm kernel shell derived bio-oil - Jamil, F. (2013)
This work investigates the comparison between upgraded product from model bio-oil and bio-oil from PKS. The process is carried out in the presence of HZSM-5 at temperature of 500Â°C, 3bar pressure and oil/catalyst ratio of 15. It is observed that the properties such as pH, density, calorific value and elemental value of products are improved. The calorific value for upgraded bio-oil is 31.65 MJ/kg while for model bio-oil the value is 30.32 MJ/kg at same operating conditions. The degree of deoxygenation of the upgraded bio-oil and upgraded model bio-oil is 43.74 and 45.56 respectively. The study showed that the model bio-oil can be used to represent the bio-oil. Â© (2013)Trans Tech Publications,Switzerland.